ANALISIS PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KECERDASAN EMOSIONAL TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN SEBAGAI VARIABEL INTERVENING (Studi Pada Karyawan PT Jasa Marga Cabang Semarang) - Aditya, Rezha; Suharnomo, Suharnomo (Faculty of Economics and Business Diponegoro University, 2017)
The purpose of this research is to find out and analyze further about Transformational Leadership and Emotional Intelligent influence on employee performance with organizational commitment as mediating variable at PT. Jasa Marga Cabang Semarang. The population in this study were all employees of PT. Jasa Marga cabang Semarang. Samples of this study are 74 employees. The techniques of data testing in this research includes the reliability test, the validity test, the classical assumption test, path analysis, and the Sobel test to examine the mediation effect with SPSS Â application. The hypothesis in this study is the transformational leadership, Emotional Intelligence, and organizational commitment has positive and significant on employee performance.